Evaluation of Quality and Antibacterial Activity of Four Brands of Ciprofloxacin Tablets Marketed in Libya - Samia Alsawi; Akram Soliman; Sara Fadil; Najwa Abdalkaream; Magbola Hussein (AlQalam Journal of Medical and Applied Sciences, 2024)
Ciprofloxacin is one of fluoroquinolones antibiotics used in treatment for infections of the urinary tract, skin and soft-tissues, and lower respiratory tract. There are many brands of ciprofloxacin tablets available in pharmacies of Albaiyda city and the aim of this study was to evaluate quality of four available brands of ciprofloxacin tablets by quality control parameters and to test their antibacterial activity. Four leading brands of ciprofloxacin tablet each with a label claim 500 mg were purchased from the various retail pharmacies of Albaiyda city and evaluated by in vitro quality control tests for tablet according to pharmacopeia (BP/ USP) that include evaluation of uniformity of weight and weight variation, friability, hardness, and disintegration time. The second evaluation was the antibacterial activity of the four brands against Klebsiella pneumonia, Staphylococcus aureus, and Escherichia coli by well diffusion susceptibility method. Weight variation for four brands of ciprofloxacin ranged from 0.507% to ,0.753%, the highest variation was found in Brand A, and the lowest weight variation was observed in Brand B and all brands comply with specification. Friability of all brands was below 1% which means that all brands have passed the test and met the specification, and the brand which most likely to be friable between brands is Brand B (0.64%) and the least likely to be friable is Brand C (0 %). The results indicated that all brands of ciprofloxacin tablets were not in the limit of hardness test and the highest hardness value was for Brand C (276 N), and the lowest hardness value was for Brand A (114.2 N). Disintegration time for four brands was under 5 minutes and all brands were complied with the both BP and USP specifications. larger zone of inhibition (ZI) for ciprofloxacin brands against Klebsiella pneumonia was found in Brand C (26.19mm) indicating that it has the highest activity and larger ZI for ciprofloxacin brands against Staphylococcus aureus was found in Brand D (40.40mm) and larger ZI for ciprofloxacin brands against Escherichia coli was also found in Brand D (21.21mm) indicating that it has the highest activity against both types of bacteria. From this study it was demonstrated that all four brands of ciprofloxacin tablet marketed in Libya comply with BP and USP specification for quality control test of uniformity of weight and weight variation, friability, and disintegration time, except that in hardness test in the four brands were found out the limit but this test is non compendial test and all the brands have similar antibacterial effect except Brand C which has slightly better microbiological activity against Klebsiella pneumonia and Brand D which is more effective against Staphylococcus aurus, and Escherichia coli. سيبروفلوكساسين هو أحد المضادات الحيوية الفلوروكينولونات ، وهو معتمد من قبل إدارة الغذاء والدواء، والذي يستخدم في علاج التهابات المسالك البولية والجلد والأنسجة الرخوة والجهاز التنفسي السفلي. وهو موجود في قائمة منظمة الصحة العالمية للأدوية الأساسية. هناك العديد من العلامات التجارية لأقراص سيبروفلوكساسين المتوفرة في صيدليات مدينة البيضاء والهدف من هذه الدراسة هو تقييم جودة أربع علامات تجارية متاحة من أقراص سيبروفلوكساسين من خلال معايير مراقبة الجودة واختبار نشاطها المضاد للبكتيريا. تم شراء أربع علامات تجارية رائدة متاحة تجاريا من أقراص سيبروفلوكساسين لكل منها مع مطالبة ملصق 500 مجم من صيدليات البيع بالتجزئة المختلفة في مدينة البيضاء وتم تقييمها من خلال اختبارات مراقبة الجودة في المختبر للأقراص وفقا لدستور الأدوية (BP / USP) والتي تشمل تقييم توحيد الوزن واختلاف الوزن ، والتفتيت ، والصلابة ، ووقت التفكك. كان التقييم الثاني هو النشاط المضاد للبكتيريا للعلامات التجارية الأربع ضد الالتهاب الرئوي الكلبسيلة والمكورات العنقودية الذهبية والإشريكية القولونية بطريقة حساسية الانتشار بشكل جيد. تراوح اختلاف الوزن لأربع علامات تجارية من سيبروفلوكساسين من 0.507٪ إلى 0.753٪ ، وتم العثور على أعلى تباين في العلامة التجارية أ ، ولوحظ أدنى اختلاف في الوزن في العلامة التجارية ب وجميع العلامات التجارية تتوافق مع المواصفات. كانت قابلية تفتيت جميع العلامات التجارية أقل من 1٪ مما يعني أن جميع العلامات التجارية قد اجتازت الاختبار واستوفت المواصفات ، والعلامة التجارية التي من المرجح أن تكون قابلة للتفتيت بين العلامات التجارية هي العلامة التجارية B (0.64٪) والأقل احتمالا أن تكون قابلة للتفتيت هي العلامة التجارية C (0٪). أشارت النتائج إلى أن جميع ماركات أقراص سيبروفلوكساسين لم تكن في حدود اختبار الصلابة وكانت أعلى قيمة صلابة للعلامة التجارية C (276 N) ، وأقل قيمة صلابة كانت للعلامة التجارية A (114.2 N). كان وقت التفكك لأربع علامات تجارية أقل من 5 دقائق وتم الامتثال لجميع العلامات التجارية لمواصفات BP و USP. تم العثور على منطقة تثبيط أكبر لماركات سيبروفلوكساسين ضد الالتهاب الرئوي الكلبسيلة في العلامة التجارية C (26.19 مم) مما يشير إلى أنه يحتوي على أعلى نشاط وتم العثور على منطقة تثبيط أكبر لماركات سيبروفلوكساسين ضد المكورات العنقودية الذهبية في تم العثور أيضا على العلامة التجارية D (40.40 مم) ومنطقة تثبيط أكبر لماركات سيبروفلوكساسين ضد الإشريكية القولونية في العلامة التجارية D (21.21 مم) ) مما يشير إلى أن لديها أعلى نشاط ضد كلا النوعين من البكتيريا. من هذه الدراسة تبين أن جميع العلامات التجارية الأربعة لأقراص سيبروفلوكساسين التي يتم تسويقها في ليبيا تتوافق مع مواصفات BP و USP لاختبار مراقبة الجودة لتوحيد الوزن واختلاف الوزن والتفتيت ووقت التفكك ، باستثناء أنه في اختبار الصلابة في العلامات التجارية الأربع تم العثور على الحد الأقصى ولكن هذا الاختبار غير اختبار شامل وجميع العلامات التجارية لها تأثير مضاد للجراثيم مماثل باستثناء العلامة التجارية C التي لديها نشاط ميكروبيولوجي أفضل قليلا ضد الالتهاب الرئوي Klebsiella والعلامة التجارية D وهو أكثر فعالية ضد المكورات العنقودية الذهبية ، والإشريكية القولونية.